Diffuse Calcifications of the Spleen in a Woman with Systemic Lupus Erythematosus - Aristeides G. Vaiopoulos; Meletios A. Kanakis; Kyriaki Katsouri; Stavroula Kyriazi; George A. Vaiopoulos; Phaedon Kaklamanis (Case Reports in Medicine)
Systemic lupus erythematosus (SLE) is a multisystemic autoimmune disease, which affects a wide variety of organs including the spleen. Splenic involvement in SLE includes conditions such as splenomegaly, hyposplenism, infarction, and spontaneous rupture. However, only a few cases of splenic calcifications in patients with SLE have been reported. Herein, we present a case of a 24-year-old female diagnosed with SLE, in which we found diffuse splenic calcifications. The unique pattern of splenic calcifications in SLE contributes to the differential diagnosis from other conditions such as infections and other connective tissue diseases, which also cause calcifications in the spleen.